Increasing the hosting capacity for renewable energy in distribution networks - MacEdo, Leonardo H. [UNESP]; Franco, John F. [UNESP]; Romero, Ruben [UNESP]; Ortega-Vazquez, Miguel A.; Rider, Marcos J. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Environmental concerns and the need to decarbonize the supply side of power systems are spurring the integration of renewable energy sources (RES). Consequently, an unprecedented increase of RES, particularly photovoltaic (PV) systems, has been observed in distribution grids. However, PV generation is weather-driven, and therefore its power production peak does not necessarily coincide with the peak demand. Therefore, large amounts of cheap renewable generation are usually spilled. This paper proposes a method for optimal allocation and sizing of energy storage systems (ESSs) to increase hosting capacity of PV generation in distribution networks. Moreover, network reinforcement and capacitor bank allocation are also considered. The problem is modeled using stochastic mixed-integer linear programming in which PV generation and demand are represented via scenarios. A 20-node test system is used to demonstrate the effectiveness of the proposed approach and to analyze the role of ESSs to improve the hosting capacity of RES.
Keywords: Distribution networks; Energy storage; Mixed-integer linear programming; Photovoltaic generation; Stochastic optimization